The Analysis of Students’ Grammatical Errors in Recount Text Writing - Nadia Nadia (Yayasan Visi Intan Permata, 2024)
Writing is a skill that requires organizing ideas into clear sentences and paragraphs, relying on a strong understanding of grammar for effective communication. However, the researcher revealed that the ninth-grade students of SMP Islam Al-Azhar 48 Samarinda frequently struggle with recounting text writing, particularly with verb tense, subject-verb agreement, and singular/plural forms. Therefore, this study aims to find out the grammatical errors in the ninth-grade students’ recount texts writing. The researcher used a qualitative approach to identify grammatical errors in recount texts written by ninth-grade students at SMP Islam Al-Azhar 48 Samarinda. Data consisted of texts collected from the students' recount writings, which were then analyzed using Oshima and Hogue's theory. The subjects were selected through purposive sampling, involving 15 ninth graders who were likely to achieve excellent English scores, with further information gathered from questioning the English teachers. The results revealed the common errors in the recount texts written by the students, including missing words, verb tense, subject-verb agreement, singular/plural forms, unnecessary words, wrong word forms, wrong word order, comma splices, fragments, and errors in prepositions, conjunctions, and articles. While students demonstrated a grasp of basic English writing rules, they still exhibited various errors, primarily due to interference from their native language and the overgeneralization of grammar rules.